Melanocyte survival and response to treatment in Vitiligo Patients - Lapiner, Vanessa (Department of Molecular and Cell Biology, 2014)
Vitiligo is a common depigmenting skin disorder with devastating psychological implications. Although evidence strongly suggests that melanocytes die in various forms of vitiligo, it is also evident, at least in certain cases, that melanocytes/melanoblasts survive in an undifferentiated stem cell form and it is from these that re-pigmentation is assumed to occur. Treatment of this distressing condition remains 'hit-or-miss' and patients' responses are unpredictable. This study aims to integrate prognostic variables such as the molecular profile of vitiliginous lesions and the patient's epidemiological profile, to develop a reliable and sensitive prognostic test enabling clinicians to plan an individualized, rational therapeutic approach for their vitiligo patients. The analysis of tyrosinase and TRP-2 mRNA expression in vitiliginous skin using quantitative RT-qPCR revealed the presence of melanoblasts/melanocytes in 60% of patients (n=21). When this survival was calculated as a percentage of the mRNA expression in the pigmented positive control specimen, it was found to range from 4% to 46% survival. Patients were subsequently treated with either potent topical corticosteroid ointment or 5% khellin cream in combination with daily sunlight exposure for 3 months and their clinical response was then assessed and correlated to the lesional melanocyte status. A good response (>50% repigmentation) was found in 3/5 patients demonstrating both tyrosinase and TRP-2 gene expression, in only 1/4 patients demonstrating TRP-2 gene expression alone and in 0/3 patients demonstrating only tyrosinase gene expression. The presence of both tyrosinase and TRP-2 mRNA expression is therefore a significant positive prognostic indicator. A significant correlation (R2 =0.8919) was found between melanocyte survival and response to khellin therapy suggesting that therapeutic modalities stimulating melanocyte proliferation and migration should be employed in patients demonstrating a melanocyte/ melanoblast reservoir. Conversely, an absence of melanocyte/melanoblast markers is predictive of a poor response to treatment with 7/9 patients lacking lesional tyrosinase or TRP-2 mRNA expression demonstrating <25% repigmentation at the conclusion of the 3 month treatment period. Therapeutic options such as surgery or cosmetic camouflage techniques should be considered for these patients. The epidemiological profile was not found to be a significant prognostic factor in predicting treatment response.